The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/uog.20115
|View full text |Cite
|
Sign up to set email alerts
|

Levator ani muscle morphology and function in women with obstetric anal sphincter injury

Abstract: Operative vaginal delivery was a risk factor for levator injury in women with OASIs, and levator injury was associated with a weaker pelvic floor muscle contraction. Special attention is recommended for women with OASI and levator injury as they would be at high risk of future pelvic floor disorders. The benefits of implementation of an intensive, focused and structured pelvic floor rehabilitation program needs to be evaluated in these women. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
2
24
1
3
Order By: Relevance
“…For proportional change in 2D levator hiatal AP diameter, the ICC of 0.81 for intrarater reliability indicates excellent reliability. The ICC (average of the three raters) of 0.82 implies excellent agreement between the raters in this population 25 , and is higher than the ICC (average of two raters) of 0.77 found in another recent publication 29 . The ICC (single measurement) of 0.61, providing information on the performance of the test in a clinical setting in which one examiner assesses one woman, is good, and the method is acceptable to use in such settings.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…For proportional change in 2D levator hiatal AP diameter, the ICC of 0.81 for intrarater reliability indicates excellent reliability. The ICC (average of the three raters) of 0.82 implies excellent agreement between the raters in this population 25 , and is higher than the ICC (average of two raters) of 0.77 found in another recent publication 29 . The ICC (single measurement) of 0.61, providing information on the performance of the test in a clinical setting in which one examiner assesses one woman, is good, and the method is acceptable to use in such settings.…”
Section: Discussioncontrasting
confidence: 52%
“…This high prevalence is in agreement with that in previous publications in women with pelvic organ prolapse scheduled for surgery 27,28 . Previous publications have found that women with major levator trauma had reduced pelvic floor contraction compared with those without trauma 6,29 . Additionally, in the present study, we found a 3-fold increased prevalence of major levator trauma among women with absent to weak contraction compared with those with moderate to strong contraction.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our study population was comprised of both primiparous and multiparous women and showed a slightly lower incidence of levator avulsions analyzed with transperineal ultrasound (n = 17, 29%). A recent study also showed a 29% prevalence of levator avulsions in conjunction with OASIS, with instrumental delivery increasing the risk of levator injury fourfold 16. The downside of transperineal ultrasound, however, could beinsufficient sensitivity in detecting OASIS.…”
mentioning
confidence: 99%